1991
DOI: 10.1083/jcb.112.4.545
|View full text |Cite
|
Sign up to set email alerts
|

A distinct vesicle population targets membranes and pore complexes to the nuclear envelope in Xenopus eggs.

Abstract: Abstract. Extracts from Xenopus eggs capable of nuclear envelope assembly in vitro were fractionated by differential and density gradient centrifugation. Nuclear envelope assembly was found to require soluble components in the cytosol and two distinct particulate fractions, which we have called nuclear envelope precursor fractions A and B (NEP-A and NEP-B). Both NEP-A and NEP-B are sensitive to treatments with trypsin, sodium carbonate, and detergents, but can be distinguished from each other by their sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
1
3

Year Published

1991
1991
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(99 citation statements)
references
References 44 publications
8
87
1
3
Order By: Relevance
“…Thus, nuclear envelope assembly required both LVs and HVs. These results agree well with those of Vigers and Lohka (1991).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, nuclear envelope assembly required both LVs and HVs. These results agree well with those of Vigers and Lohka (1991).…”
Section: Discussionsupporting
confidence: 92%
“…The first step is the binding of vesicles with the chromatin, and the second step is the fusion of vesicles on the chromatin. Vigers and Lohka (1991) reported that nuclear envelope assembly in cell-free extracts requires two distinct vesicles, called NEP-A and NEP-B. They showed that only NEP-B binds to sperm chromatin, but nuclear envelope assembly requires these two vesicles.…”
Section: Two Distinct Vesicles Lvs and Hvs Are Required For Nuclearmentioning
confidence: 99%
See 1 more Smart Citation
“…S1), consistent with the well-known fact that NE formation in vitro requires both soluble and membrane components of the egg (Vigers and Lohka, 1991;Goldberg et al, 1997;Gant and Wilson, 1997). The light membranes alone (labeled with DiOC 18 , green emitting) did not bind to chromatin and a nuclear membrane did not form (Fig.…”
Section: Introductionsupporting
confidence: 68%
“…Whether this is due to lateral diffusion within the membrane or to vesicle formation and fusion is an open question. In certain cases, extensively exemplified by Xenopus eggs, integral membrane proteins of the nuclear membrane are found in distinct vesicles (Vigers and Lohka, 1991;Buendia and Courvalin, 1997;Drummond et al, 1999). Indeed, recent reports suggest that there are multiple populations of specialized vesicles (Antonin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%